The role of glutamate decarboxylase 65 in gastric cancer development, progression, and prognosis. Issue 3 (3rd July 2013) - Song, Yongxi; Li, Shizheng; Wang, Zhenning; Zhu, Jinliang; Gao, Peng; Wang, Meixian; Dong, Yulan; Xu, Huimian
Abstract : Aims: Recent studies have revealed that glutamate decarboxylase 65 (GAD65) plays important roles in cancer progression. The role of GAD65 in gastric cancer development, progression and prognosis is currently unknown, and we aimed to investigate this. Methods and results: Immunohistochemistry revealed that GAD65 expression in 313 gastric cancer tissues was significantly higher than in 60 adjacent non‐tumour tissues. Moreover, the expression level of GAD65 significantly correlated with the depth of tumour invasion and TNM stage. GAD65 expression level was a significant prognostic factor in univariate survival analysis, but did not remain an independent prognostic factor following Cox multivariate analysis. For tumours with an intermediate type growth pattern, when those showing low expression of GAD65 were reclassified with expanding type tumours, and those showing high expression with infiltrative type tumours, there was a significant difference in prognosis between these two novel subgroups, and this remained a significant prognostic factor in multivariate analysis. Conclusions: Our findings indicate that GAD65 is involved in the development and progression of gastric cancer as a tumour oncoprotein. Further elucidation of the molecular mechanisms underlying the role of GAD65 is warranted.